INDIGENOUS IN HIGHER EDUCATION AND INTERCULTURAL POSSIBILITIES OF DIALOGUE. THE EXPERIENCE OF THE RED DE SABERES PROGRAM-MS/BRAZIL - Antonio Hilario Aguilera Urquiza (Universidad Nacional del Nordeste, 2016)
This paper aims to deepen the conceptual and epistemological reflection about the dialogue between traditional knowledge and knowledge considered "Western", in the context of indigenous in public universities in the state Mato Grosso do Sul (Brazil). This area has the largest number of indigenous pursuing higher education of the country, around 900 students. Could be the frequency of indigenous in higher education be understood as a strategy of struggle to build their autonomy processes? Could be understood indigenous and universities relation as a coloniality relationship or the possibility of building self-determination of these people? This paper is the result of a research in progress, with the following methodological procedures: first, the documentary and bibliographic research, intending to read the student experiences by some authors and theorists such as Hall (2000), Bhabha (2003), Mignolo (2003), Freire (1970; 1992), Quijano (1992), Mato (2008; 2014; 2015), Aguilera Urquiza e Nascimento (2013), followed by fieldwork experience, performed by semi-structured interviews with indigenous students who compose the "Programa Rede de Saberes- permanência de indígenas na educação superior", in particular those who have completed graduation.